Reflexões sobre a reforma da previdência de 2019 e seus impactos nos RPPS - Guimarães, Stênio Leão (2024)
This study aims to analyze the 2019 social security reform and its impacts on the largest municipal and state RPPS in each Brazilian region regarding the calculation of social security benefits. Social policies have gone through periods of expansion and concentration of rights over time. In the 1950s, there was a proposal to unify social security legislation for the private sector, resulting in the creation of the Organic Law of Social Security. Subsequently, the National Institute of Social Security was created and incorporated the Retirement and Pension Institutes, as well as the Institute of Social Security and Assistance of State Employees. It was only in 1988, with the promulgation of the Citizen Constitution, that the civil service began to have its own separate social security system. In view of this scenario, more than two thousand entities of the federation established the Proper Social Security Regime (RPPS) for civil servants in permanent positions. However, the 2019 social security reform brought changes to the own regimes, requiring changes in local legislation. In addition, some constitutional provisions now prohibit the creation of new RPPS and opened the possibility of their extinction. Through a bibliographic research in doctrine and legislation, the structure of social security for public servants based on the principle of solidarity and dignity of the human person will be addressed. It will also analyze the problem of conducting social security in the face of economic crises and the need to promote fiscal adjustments, with emphasis on discussions on the search for a balanced protection system without giving up promoting solidarity and social justice. Through a legislative research, in view of the freedom established by EC No. 103/2019 for each entity to set its own rules, the reaction of the largest state and municipal RPPS in each Brazilian region will be analyzed when defining the way of calculating retirement and civil pension for death benefits.